DNA assisted regioregular poly (3, 3‴-didodecylquarterthiophene), rr-PQT-12 fiber: Organic bio-electronic devices - Singh M.K.; Kumar A.; Prakash R. (My University, 2025)
Present work has focused on the development of bio-organic hybrid materials based on hydrophobic DNA-complex incorporated in polymer and the study of charge transport properties across the junction formed by sandwiching it between conducting electrodes (called hetero-structured vertical diode). The inclusion of hydrophilic DNAs, both natural DNA and synthetic DNA (single strand DNA, ss-DNA and double strand DNA, ds-DNA), in organic semiconducting polymer specially regioregular poly (3, 3‴-didodecylquarterthiophene) (rr-PQT-12), have done in chloroform. Prior to DNAs inclusion, hydrophobic DNA-DDAB complexes have formed by reaction of hydrophilic DNA and didodecyldimethylammonium bromide, DDAB in aqueous solvent. Thereafter, as-mixed solution has been aged for 45 min to obtain fibrils’ growth and used for the fabrication of devices. Various parameters including rectification ratio, ideality factor, saturation current, barrier height and device stability have been measured to study the nature of charge transport and effect of DNAs on the performance of devices. The device performance has been observed better with the incorporation of G-C rich DNAs. ds-DNA based devices exhibit improved rectification ratio i.e. two times higher than that of ss-DNA and three times higher than that of rr-PQT-12 with least turn-on voltage (0.56 V) or even low ideality factor (3.02), due to hot carrier injection phenomenon by assembled rr-PQT-12 to nearby nucleotide bases. © 2017 Elsevier B.V.